(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Current investigation was to develop gastro retentive floating microsphere for Ropinirole. These microspheres of Ropinirole were prepared by ionic gelation method with an aim of increasing the gastric residence time and for controlled release. Sodium alginate, HPMCK15, Gaur gum was used as polymers. Sodium bicarbonate was used as the gas-forming gent. Prepared microspheres were characterized for micromeretic properties, entrapment efficiency, buoyancy study, SEM analysis, FTIR, and in vitro dissolution studies. Among 14 formulations F12 was found to be optimized and based on the evaluation parameters. The % buoyancy, % yield, % entrapment efficiency and swelling index of F12 formulation was 94.50, 97.58, 98.10% and 96.14%, respectively. The Cumulative % drug release of F12 formulation was 98.16 ± 5.15 in 12 h when compared with marketed product 90.16 ± 5.00 in 12 h. SEM studies showed the particles were in spherical shape. Hence the formulated floating Ropinirole microspheres may establish to be potential candidate for safe and effective sustained drug delivery and improve the bioavailability in the effective management of Parkinson’s disease.